(untitled) (Vietnam Journal of Community Medicine, 2022)
Question: Microdissection testicular sperm extraction (micro tese) is a highly effective method of sperm collection with a low risk of secondary testicular damage. Objectives: To evaluate the sperm collection rate by microtese method in patients with nonobstructive azoospermia (NOA) and some related factors. Subjects and research methods: 132 NOA patients were micro-tese made at the Military Clinical Embryo Institute - Vietnam Military Medical University from 5/2017 to 12/2019. Results: The sperm collection rate was 40.15%. There was no association between age, BMI, duration of infertility, AZF with sperm collection rate. There was a relationship between testicular volume, hormone concentration, histopathology, and sperm collection rate. The cut-off point of the right and left testicular volumes were 5.5mL, with a sensitivity of 86.3% and 84.3%, specificity of 50.6% and 51.9%, and a curve area of 0.707, respectively and 0.676 (p < 0.001 and p < 0.01). The cut-off points of FSH, LH and testosterone were 13.41mIU/ mL, 7.64mIU/mL and 3.02ng/mL, respectively, with a sensitivity of 74.4%; 69.9%; 86.8%, specificity 58.5%; 56.6%; 46.8% and the corresponding curve area was 0.666; 0.625; 0.647. Conclusion: Although the relationship between testicular volume, FSH, LH, testosterone levels, and histopathology with microtese sperm collection rate in NOA patients was found, the prognostic value was low.